No dose response effect of carbohydrate mouth rinse on cycling time-trial performance - James, R. M.; Ritchie, S.; Rollo, I.; James, L. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
The aim of the current study was to investigate the influence of mouth rinsing carbohydrate at increasing concentrations on ~1 hr cycle time trial performance. Eleven male cyclists completed three experimental trials, following an overnight fast. Cyclists performed a ~1 hr time trial on a cycle ergometer, while rinsing their mouth for 5 s with either a 7% maltodextrin solution (CHO), 14% CHO or a taste-matched placebo (PLA) after every 12.5% of the set amount of work. Heart rate was recorded every 12.5% of the time trial, while RPE and GI comfort were determined every 25% of the time trial. The mouth rinse protocol influenced the time to complete the time trial (p < .001), with cyclists completing the time trial faster during 7% CHO (57.3 ± 4.5 min; p = .004) and 14% CHO (57.4 ± 4.1 min; p = .007), compared with PLA (59.5 ± 4.9 min). There was no difference between the two carbohydrate trials (p = .737). There was a main effect of time (P<0.001) for both heart rate and RPE, but no main effect of trial (p = .107 and p = .849, respectively). Scores for GI comfort ranged from 0-2 during trials, indicating very little GI discomfort during exercise. In conclusion, mouth rinsing and expectorating a 7% maltodextrin solution, for 5 s routinely during exercise was associated with improved cycle time trial performance approximately 1 h in duration. Increasing the carbohydrate concentration of the rinsed solution from 7% to 14% resulted in no further performance improvement.